ESTUDO DOS PROBLEMAS TÉCNICOS DA CULTURA DE CANA-DE-AÇÚCAR (Saccharum Officinarum.) - Quadros, Valmir J. d.; Buratti, João V.; Silva, José A. G. d.; Abreu, Fernando B.; Batistti, Gabriel (Salão do Conhecimento, 2013)
Resumo